Amoxicillin or tetracycline in bismuth-containing quadruple therapy for Helicobacter pylori eradication: a systematic review and meta-analysis - Ju, Kunping; Kong, Qingzhou; Zhang, Shanling; Zhu, Liangrun; Li, Yueyue (Frontiers in Microbiology, 2025)
BackgroundAmoxicillin and tetracycline have been widely used in Helicobacter pylori (H. pylori) eradication therapy, and the priority of their efficacy and safety in Bismuth-containing Quadruple Therapy (BQT) remain controversial.Materials and methodsA comprehensive systematic review was conducted by searching databases from their inception until June 2025. Studies that compared BQT arms containing amoxicillin with those containing tetracycline were included. Pooled Relative Risks (RR) and 95% Confidence Intervals (CI) of the efficacy and safety outcomes were reported.ResultsSeven randomized controlled trials and two observational studies were included in the meta-analysis. The pooled eradication rates of amoxicillin-containing BQT versus tetracycline-containing BQT in the first-line treatment were not statistically different in the intention-to-treat (86.5% vs. 81.4%, RR: 1.07, 95% CI: 0.99−1.17, P = 0.10) and per-protocol (93.3% vs. 90.7%, RR: 1.03, 95% CI: 0.97−1.10, P = 0.34) analyses. The eradication rates for rescue therapy yielded similar results in the ITT (81.1% vs. 89.7%, RR: 0.90, 95% CI: 0.79−1.03, P = 0.13) and PP (85.1% vs. 93.4%, RR: 0.91, 95% CI: 0.80−1.03, P = 0.14) analyses. The risk of total adverse events was lower in the amoxicillin-containing BQT than in the tetracycline group (26.8% vs. 37.1%, P < 0.00001). No difference in total compliance (94.8% vs. 92.8%, P = 0.20).ConclusionThe efficacy of both amoxicillin- and tetracycline-containing BQT demonstrated comparable eradication rates and compliance, while the amoxicillin group exhibited fewer adverse events.